COMMUNITY BASED EDUCATION INOVATION IN KAMPOENG SINAOE SIDOARJO - Nur Aini Firda Rosyida; Triana Rosalina Noor (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to describe the educational innovations at Kampoeng Sinaoe, Sidoarjo, by using a qualitative case study approach. The data collection techniques used observation, documentation, and interviews ti the institution's management, coordinators, teachers, alumni, and local residents, who were selected through snowball sampling. The collected data were analyzed through the stages of data collection, data presentation, drawing conclusions and triangulation of methods and sources, researchers ensure the validity of the data.  The study showed that the community-based educational innovations implemented by Kampoeng Sinaoe Sidoarjo include strengthening teacher competencies, character education based on religious and ecological values, the provision of facilities, learning activities, and program diversification. These innovations serve as strategic efforts to improve the quality of learning in non-formal educational institutions through a holistic approach that addresses local needs and contemporary developments, aiming to create a meaningful, inclusive, and sustainable educational process.